The Evolving Functions and Organization of Finance Ministries - Allen, Richard (IMF Working Papers; Working Paper ;, 2015)
There is relatively little literature that analyses the role, functions, and organization of finance ministries. The purpose of this working paper is to review international experiences in this area, in an effort to formulate guiding principles of organizational design and the allocation of functions, while recognizing the crucial importance of each country's history and institutional context. Over the past 30 years many finance ministries have moved from a 'traditional' to an 'emerging' model of organizational design in which there is greater openness and transparency, more flexible management practices, and a broader focus on strategic policy issues. In addition, many operational functions have been devolved to arm's-length agencies or line ministries. The paper describes the challenges facing developing countries in strengthening their finance ministries, and the principles, approaches, and strategies that can be applied.